Is There a Law Instinct? - Michael D. Guttentag (Washington University Law Review, 2009)
The widely held view is that legal systems develop in response to purposeful efforts to achieve economic, political, or social objectives. An alternative view is that reliance on legal systems to organize social activity is an integral part of human nature, just as language and morality now appear to be directly shaped by innate predispositions. This Article formalizes and presents evidence in support of the claim that humans innately turn to legal systems to organize social behavior.
Keywords: Jurisprudence; Language; Morality; Organization of social behavior